Dynamic of kayak rowing technique in the process of competition activity - A.N. Kolumbet (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Urpose: To study the dynamic of kayak rowing technique in the process of competition activity and influence of special physical qualities on technique of athletes' movements. Material: in the research 17 elite athletes participated. Results: it was found that with boat speed the values of maximal and average efforts, applied by athlete to oar; duration of efforts; the moment of torso turn start in respect to water catching and in the moment of stroke fulfillment confidently and steadily correlate. The studies showed that power of stroke plays decisive role for speed sustaining at the beginning and in the middle of distance. By the end of distance the significance of indicators, characterizing effectiveness of athletes' movements; boat motion during strike; duration of efforts noticeably grow. Conclusions: dynamic of rowing technique is pre-conditioned by re-constructions of system of movements at different levels of its organization and control. Constant and substantial varying of contribution of movements system's secondary elements conditions stability and effectiveness of movements' biomechanical characteristics and workability indicators.